The Impact of Factory-to-Costumer Business Model on MSMEs in Indonesia: An Islamic Business Ethics Perspective on Temu Application - Daulay, Ulan Dari (Perbanas Journal of Islamic Economics and Business, 2025)
This study investigated the impact of the factory-to-customer (F2C) business model, implemented by the Temu application, on the sustainability of local Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The F2C model allows consumers to buy products directly from manufacturers without intermediaries. Although it offers lower prices for consumers, it raises serious concerns for local businesses that struggle to compete with imported goods. This research uses a descriptive method with a qualitative approach. Relevant journal articles, books, and reports were selected through purposive sampling. The collected data were analyzed by comparing sources and identifying key ethical and economic issues. The findings indicate that F2C business practices, purported to be highly efficient and lucrative, contravene Islamic business ethics, specifically justice (adl), transparency (bayan), and the prohibition of uncertainty (gharar). These practices have the potential to engender inequitable competition and disrupt market equilibrium. This research makes a novel contribution to the Islamic economic discourse by underscoring the significance of fair regulation and the role of the government in overseeing digital business practices. The implications of this research underscore the necessity to fortify national regulations grounded in Islamic ethical values, thereby ensuring the sustainability of local MSMEs within the expanding digital business ecosystem.